Mediating and Moderating Mechanisms in the Relationship Between Social Media Use and Adolescent Aggression: A Scoping Review of Quantitative Evidence - Georgios Giannakopoulos; Afroditi Prassou (European Journal of Investigation in Health, Psychology and Education, 2025)
Adolescents’ pervasive use of social media has been increasingly linked to aggression, including cyberbullying and hostile online interactions. While this association is well documented, the psychological and contextual mechanisms that mediate or moderate it remain unclear. This scoping review maps quantitative evidence on mediators and moderators between social media use and aggression among adolescents. A comprehensive search using ProQuest’s Summon platform was conducted across PsycINFO, Scopus, PubMed, and Web of Science, following the PRISMA 2020 guidelines. Eligible studies, published between January 2020 and March 2025, included adolescents aged 11–18 and reported at least one statistical mediation or moderation analysis. Forty-four studies from 19 countries (N > 90,000) were thematically synthesized. Key mediators included problematic use, moral disengagement, depression, attention-seeking, and risky digital behaviors. Moderators included gender, body satisfaction, cultural setting, school type, and family attachment. Most of the studies used structural equation modeling or PROCESS macro, although cross-sectional designs predominated. Limitations included reliance on self-reports and inconsistent social media measures. The findings suggest that social media–aggression links are indirect and shaped by emotional, cognitive, and ecological factors. Multi-level interventions targeting digital literacy, moral reasoning, and resilience are needed. This review was not registered and received no external funding.